Goals and challenges in hybrid software development approaches. Issue 11 (24th September 2021) - Prenner, Nils; Unger‐Windeler, Carolin; Schneider, Kurt
Abstract: The number of companies that use agile methods increases steadily. However, these companies often do not implement a pure agile approach but combine agile and plan‐based methods to so‐called hybrid development approaches. However, the development of these approaches is rather difficult for the companies, since agile and plan‐based approaches often follow opposite concepts. To benefit from agile and plan‐based approaches at the same time, the companies have to identify and address the conflicts between agile and plan‐based methods. The conflicts depend on the goals that are pursued with the implementation of agile and plan‐based methods. However, there is no overview of the exact goals that are pursued in hybrid approaches and which challenges and conflicts arise with them. Therefore, we conducted a systematic mapping study to gather and analyze the goals and challenges in hybrid development approaches. The mapping study is focused on literature that presents the actual needs and goals of companies and projects. Based on our results, we present the influence factors that cause conflicts in hybrid approaches and discuss how these conflicts can be addressed. Abstract : This work investigates the goals that are pursued in hybrid approaches and how these goals are addressed in the context of a systematic mapping study. Further, it identifies conflicts and challenges that arise in hybrid approaches by a simultaneous use of agile and plan‐based methods for the same activity. In order to guide practitioners in the creation of hybrid approaches, the authors discuss how these conflicts can be addressed.